Analisis Pengaruh Struktur Pasar dan Perilaku Pasar Terhadap Kinerja Pasar Pada Bank Umum Syariah di Indonesia dan Malaysia Tahun 2011-2015 - Rachma Revida; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The aim of this study was to analyze the influence of market concentration, market share, and OEOR on profitability in Islamic Banks in Indonesia and Malaysia in 2011 – 2015 using the paradigm of structure, conduct, and performance. The samples of the study consisted of a total 11 Islamic banks in Indonesia and 16 Islamic banks in Malaysia. The analysis technique use in this study was panel data regression using Eviews 7.0 programme. The independence variables of the study were market concentration ratio Herfindahl-Hirchman index), market share, and OEOR, while the dependent variable was the return of asset (ROA). The results of this study indicate that market concentration and market share variables not significantly affect the ROA of Islamic banks in Indonesia and Malaysia, while the OEOR variable has significant effect to the ROA of Islamic banks in Indonesia and Malaysia.